SOCIALIZATION OF THE IMPORTANCE OF HYGIENIC Snacks in GORONTALO CITY TRADITIONAL MARKETS - torajasa achamar (LPPM Universitas Bina Mandiri Gorontalo, 2023)
The purpose of this research is: To know the description of street food from the aspect of the Importance of Hygiene Snacks in Traditional Markets in Gorontalo City, Gorontalo City. Methods: This research is a type of descriptive research using a qualitative approach in the form of observation, interviews and laboratory tests. Samples were taken by purposive sampling method, as many as 20 street food vendors in the Traditional Market of Gorontalo City. The results showed that all 20 traders did not get used to scratching their bodies near food and all traders had used equipment for serving food, used clean or proper clothes, and brought sweat cleaners. All traders are still not used to washing their hands. There are 15 traders who serve snacks without using closed containers. E. Coli microbiological test results, not found E. Coli in all food samples examined. Conclusion: the hygiene of the seller needs to be improved, especially wearing an apron and washing hands. The safety of street food is good because there is no microbiology of E. Coli bacteria found. Traders should try to always wear an apron and should maintain hand hygiene.